House Price Synchronicity, Banking Integration, and Global Financial Conditions - Alter, Adrian (IMF Working Papers; Working Paper, 2018)
We examine the relationship between house price synchronicity and global financial conditions across 40 countries and about 70 cities over the past three decades. The role played by cross-border banking flows in residential property markets is examined as well. Looser global financial conditions are associated with greater house price synchronicity, even after controlling for bilateral financial integration. Moreover, we find that synchronicity across major cities may differ from that of their respective countries', perhaps due to the influence of global investors on local house price dynamics. Policy choices such as macroprudential tools and exchange rate flexibility appear to be relevant for mitigating the sensitivity of domestic housing markets to the rest of the world.